Desarrollo de una propuesta para la obtención de un aceite de THC y/o CBD por el método de extracción con solvente (2020)
The following degree work originates from identifying the growing need of the world market for cannabis oil, being the objective of this to make a proposal for obtaining a THC and/or CBD oil using the method of extraction with solvent. Initially the generalities of the plant were identified, defining the varieties of cannabis present, as well as the generalities of cannabis cultivation, displaying the advantages that Colombia presents compared to other countries, once this was known, the investigation proceed to the investigation of the different methods of extraction with solvent present in the state of the art, establishing the ranges and conditions of operation of those, to proceed with the next part of the work. Later a selection of the method of obtaining the oil was made, comparing between the selected methods, making use of resources like the Pugh matrix, once selected once selected, a bibliographic study was carried out on the variables present in the process, defining how those affect teorically the process, comparing between different authors in order to determine the conditions of operation that would be used in following escalation of the process.